(untitled) (International journal of artificial intelligence, 2026)
This article explores the enhancement of literacy teaching methodologies for preschool children aged 5-6 through a facilitative approach rooted in humanistic psychology, primarily drawing from Carl Rogers' principles. Traditional teacher-directed methods are contrasted with facilitative strategies that position the educator as a guide, fostering child-led exploration, play-based learning, and meaningful interactions in print-rich environments. The study integrates international best practices with Uzbekistan's "Ilk Qadam" (First Step) curriculum, emphasizing phonemic awareness, oral language development, print concepts, and emergent writing. A mixed-methods methodology involving teacher training, classroom implementation, and pre/post assessments demonstrates significant improvements in children's literacy skills, motivation, and engagement. Findings highlight the effectiveness of guided play, responsive scaffolding, and supportive emotional climates in accelerating literacy acquisition while respecting developmental stages. Recommendations include professional development for teachers and integration of culturally relevant materials. This approach aligns with global early childhood education standards and Uzbekistan's reforms toward competency-based, play-oriented preschool education.